Legal Protection for Fixed-Term Employment (PKWT) Workers Against Unilateral Contract Termination Based on Labor Law from a Labor Law Perspective - Michelle Christie (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The prevalence of unilateral termination of employment contracts for workers with a Fixed-Term Employment Agreement (PKWT) indicates the weak legal protection in labor practices. This study aims to analyze the regulation of PKWT and the effectiveness of legal protection against unilateral contract termination from a labor law perspective. The method used is normative legal research with statutory and conceptual approaches. The results show that although the legislation regulates the prohibition of unilateral termination and the obligation to provide compensation, its implementation has not been optimal. This is influenced by workers’ low awareness of their rights, weak bargaining positions, and limited access to dispute resolution mechanisms. Therefore, strengthening supervision and increasing legal awareness are necessary to ensure more effective protection for workers.